Analyzing UI and UX of Verval PTK: Impact on Elementary School Data Precision - Huda, Shamsul; Wardoyo, Ari Eko; Sulistyo, Henny Wahyu (Politeknik Ganesha Medan, 2024)
This study explores the implementation of the Verval PTK application in elementary school data management in Kabupaten Jember, with emphasis on its impact and precision. The research methodology adopts a differential qualitative descriptive design, with the main focus on elementary schools in Kabupaten Jember that have integrated Verval PTK. Five Elementary Schools were involved in the study. Among others, SD Negeri Jember Lor 2, SD Negeri Kepatihan 1, SD Negeri Jember Kidul 2, SD Negeri Kebonsari 1, and SD Negeri Patrang 1. In the analysis, the study involved technical aspects such as usability tests, performance measurements using Lighthouse, and A/B tests. However, challenges related to platform accessibility and stability are still a concern. Performance measurement using Lighthouse shows excellent scores, although SEO scores require further attention to improve. A/B tests highlight significant improvements in time efficiency and data accuracy through Verval PTK implementations, but some low scores require more in-depth analysis. A number of technical recommendations were put forward to improve the security, stability, accessibility, and SEO optimization of Verval PTK. Regular software updates, efficient error management, and real-time performance monitoring are key focuses to support continuous development. This recommendation is directed to strengthen the role of Verval PTK in supporting efficient and accurate school data management.